Integrity, Vulnerability, and Temporality - Traina, Cristina L. H. (De Ethica, 2023)
This paper asks how to account for vulnerable integrity in the temporal dynamism of human lives without relying on a subtractive vision of integral human nature, borrowing from presumed past or future rationality and maturity, or depending on an external attribution of dignity. Illustrating the challenges with vignettes from the author’s life, it argues inductively that human integrity includes morally inviolable vulnerability to others with whom we are in interdependent relationship and without whom we cannot develop or maintain our selves. Others reside at the core of our integrity, for better and for worse, and we reside at theirs. Augustine’s accounts of memory, time, and the narrative self; Whiteheadian process thought’s understanding of continuity through change; and feminist theories of narrative all provide theological and philosophical justifications for this vision of integrity. John Wall’s and Johan Brännmark’s non-foundational approaches to integrity and human rights lead us to the same conclusion without entailing theological anthropological claims, ensuring its relevance in a pluralist culture.